2014
DOI: 10.1002/gj.2586
|View full text |Cite
|
Sign up to set email alerts
|

Wind regimes and aeolian geomorphology in the western and southwestern Tengger Desert, NW China

Abstract: Wind is the primary control on the formation of aeolian geomorphology. In this study, we combined wind regime data from automated weather stations in the western and southwestern Tengger Desert of the Inner Mongolia region in China with remote‐sensing data to analyse the relationship between the wind energy environment and aeolian geomorphology. Tengger Desert is one of the main dust storm sources in northwestern China. Therefore, efforts aimed at controlling desertification and dust storm require a deeper und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
(106 reference statements)
3
5
0
Order By: Relevance
“…In the study area, Mz was fine at the crest, which was similar to the findings by Lancaster [36] and Livingstone et al [37]. However, there were three types (coarser, finer, or no difference between the windward slope and leeward slope) of Mz variations over the dune surfaces in the Tengger Desert and Hexi Corridor Desert [14,15].…”
Section: Grain Size Parameterssupporting
confidence: 88%
See 3 more Smart Citations
“…In the study area, Mz was fine at the crest, which was similar to the findings by Lancaster [36] and Livingstone et al [37]. However, there were three types (coarser, finer, or no difference between the windward slope and leeward slope) of Mz variations over the dune surfaces in the Tengger Desert and Hexi Corridor Desert [14,15].…”
Section: Grain Size Parameterssupporting
confidence: 88%
“…In a study that was performed approximately 60 km downwind of our study area, Zhang and Dong [35] reported that the sand was mainly moderately sorted (46%) and well sorted (29%), the skewness is mainly symmetrical (40%) and negative (27%), and the kurtosis is mainly mesokurtic (37%) and platykurtic (29%). Based on the findings from the study area and those of [15], the sorting increased, the skewness graded toward symmetrical, and the kurtosis graded toward mesokurtic, with an increasing distance downwind that was consistent with the conclusions that were developed by Zhang et al [15] from a study that was performed in the Hexi Corridor Desert. Figure 9 shows the grain size parameters (mean grain size, sorting, skewness, and kurtosis) in the study area.…”
Section: Grain Size Parameterssupporting
confidence: 85%
See 2 more Smart Citations
“…With an area of 4.27 × 10 4 km 2 , it is the fourth largest desert in China, and is bordered by the Helan Mountains to the east, the Yabulai Mountains to the northwest, and the Qilian Mountains to the southwest. The average altitude is 1200-1400 m [18,19]. The local weather is controlled by westerly circulation.…”
Section: Study Areamentioning
confidence: 99%